Political resilience through voting cohesion in the information age - Kostiuk, Tetiana (Skhid, 2026)
The article examines the challenge of ensuring the political resilience of democratic systems in the information age. The author analyzes the transformation of electoral processes driven by pervasive digitalization, framing electronic voting (e-voting) not merely as a technical instrument but as a strategic mechanism for fostering political cohesion and inclusivity. It is emphasized that the virtualization of the political sphere necessitates a clear understanding of new interaction algorithms among all stakeholders. The study elucidates the dualistic nature of e-voting, contrasting its potential to enhance civic engagement and the risks of social polarization and vulnerability to digital threats, particularly disinformation. Specific attention is devoted to safeguarding democratic integrity against the erosion of social cohesion amidst global turbulence. The relevance of the research is further amplified by the context of the ongoing war in Ukraine which creates an urgent need to modernize electoral legislation and establish inclusive conditions for political participation across all population strata. Applying a case study method (referring to the experiences of Estonia, France, Sweden, and Switzerland) and the elements of SWOT analysis, the author integrates European digital transformation practices with the challenges the Ukrainian state institutions are facing. The findings substantiate the necessity of a comprehensive approach to implementing e-voting in Ukraine, encompassing legislative reform, the development of secure technological infrastructure (leveraging the Diia ecosystem), and the implementation of strategies to advance digital literacy and public trust.